Can young members of Slovene minorities in neighbouring countries be useful for Slovenia’s diplomacy? - Udovič, Boštjan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
The article deals with the issue of incorporating young members of Slovene minorities in neighbouring countries into Slovenia’s diplomatic and foreign policy activities. The key precondition for this is the perception of Slovenia as their kin-state. The paper brings two main findings: the first is that a definition of kin-state as a unique concept is problematic, since it changes with different variables. The second finding refers to a concrete case study of young members of Slovene minorities in neighbouring countries, who have different contexts and perceptions of Slovenia (and Slovenehood). This means that Slovenia needs a comprehensive overhaul – and adaption to different conditions – of its own understanding of its ethnic minorities in the neighbouring countries if it wishes to include its young kin in Austria, Croatia, Hungary and Italy in its foreign policy and diplomacy.
Keywords: Avstrija; diplomacija; Hrvaška; Italija; Madžarska; manjšine; mladi; Slovenija